Pollution Emissions, Environmental Policy, and Marginal Abatement Costs - Ling-Yun He (International Journal of Environmental Research and Public Health, 2017)
Pollution emissions impose serious social negative externalities, especially in terms of public health. To reduce pollution emissions cost-effectively, the marginal abatement costs (MACs) of pollution emissions must be determined. Since the industrial sectors are the essential pillars of China’s economic growth, as well as leading energy consumers and sulfur dioxide (SO2) emitters, estimating MACs of SO2 emissions at the industrial level can provide valuable information for all abatement efforts. This paper tries to address the critical and essential issue in pollution abatement: How do we determine the MACs of pollution emissions in China? This paper first quantifies the SO2 emission contribution of different industrial sectors in the Chinese economy by an Input-Output method and then estimates MACs of SO2 for industrial sectors at the national level, provincial level, and sectoral level by the shadow price theory. Our results show that six sectors (e.g., the Mining and Washing of Coal sector) should be covered in the Chinese pollution emission trading system. We have also found that the lowest SO2 shadow price is 2000 Yuan/ton at the national level, and that shadow prices should be set differently at the provincial level. Our empirical study has several important policy implications, e.g., the estimated MACs may be used as a pricing benchmark through emission allowance allocation. In this paper, the MACs of industrial sectors are calculated from the national, provincial and sectoral levels; therefore, we provide an efficient framework to track the complex relationship between sectors and provinces.